Natural disasters - "Brian Janeen"; Brian, Janeen Janeen Margaret; Era Publications (South Australia Era Publications, 1991)
Provides an in-depth look at seven different types of natural disasters that occur on Earth, including earthquakes, volcanoes, floods, hurricanes, tornadoes, droughts, and tsunamis. The book explains the causes and effects of these disasters and discusses safety measures and preparedness strategies.
Includes index
Primary school students
Keywords: Natural disasters